Comparison of outcomes with vancomycin or metronidazole for mild‐to‐moderate Clostridium difficile associated diarrhea among solid organ transplant recipients: A retrospective cohort study. Issue 3 (30th March 2018) - Nguyen, Cynthia T.; Li, Julius; Anders, Stephanie; Garcia‐Diaz, Julia; Staffeld‐Coit, Catherine; Hand, Jonathan
Abstract: Background: Current guidelines recommend oral vancomycin or fidaxomicin for the treatment of mild‐to‐moderate Clostridium difficile associated diarrhea (CDAD), while metronidazole is recommended as an alternative when oral vancomycin and fidaxomicin are unavailable. However, data are lacking among the solid organ transplant (SOT) population. Methods: This single center, retrospective cohort study evaluated adult SOT recipients with mild‐to‐moderate CDAD. Analysis 1 evaluated patients receiving initial therapy with metronidazole vs oral vancomycin for at least 72 hours. Analysis 2 evaluated patients receiving metronidazole vs oral vancomycin for at least 70% of the treatment duration. The primary outcome was treatment failure. Secondary outcomes included CDAD recurrence and all‐cause mortality. Results: Analysis 1 included 71 patients (metronidazole n = 50, oral vancomycin n = 21) and analysis 2 included 75 patients (metronidazole n = 42, oral vancomycin n = 33). No significant differences in C. difficile risk factors were observed between groups in either analysis. However, in both analyses, more patients in the oral vancomycin arm received antibiotics during the CDAD episode (analysis 1, 52% vs 26%, P  = .03; analysis 2, 55% vs 32%, P  < .01). Neither analysis demonstrated differences in treatment failure (analysis 1, metronidazole 16%, oral vancomycin 10%, P  = .71; analysis 2, metronidazole 2%, oral vancomycin 6%, P  = .58). CDAD recurrence and all‐cause mortality were similar across groups in both analyses. Conclusions: Results suggest that both metronidazole and oral vancomycin are reasonable options for the treatment of mild‐to‐moderate CDAD in patients with SOT. No difference in treatment failure was observed; however, oral vancomycin may be preferred for higher risk patients, such as those receiving concurrent antibiotics.